Does sustainability matter at tourism sites? Impact of motivation and employee-ambidexterity on employee-innovative-behaviour - Bitrus Zinga Danlami; Monica Clarkson Gajere (Goodwood Publishing, 2023)
Purpose: The sustainability of tourism sites in plateau states has been a significant concern. This study aims to analyze the impact of motivation (intrinsic and extrinsic) and employee ambidexterity on innovative employee behavior on the sustainability of tourism sites in Nigeria. Research Methodology: A quantitative approach was adopted and a questionnaire-based survey was conducted among employees of five government tourism sites in Plateau State, Nigeria. A total of 163 responses were received and multiple regression analyses were conducted using Smart-PLS version 3.2.7. Results: The results revealed that (a) intrinsic motivation significantly impacts innovative employee behavior, (b) extrinsic motivation significantly impacts innovative employee behavior, (c) intrinsic motivation significantly impacts employee ambidexterity, (d) extrinsic motivation significantly impacts employee ambidexterity, (e) employee ambidexterity significantly impacts employee innovative behavior, (f) employee ambidexterity mediates the relationship between intrinsic motivation and employee innovative behavior, and (g) employee ambidexterity mediates the relationship between extrinsic motivation and innovative employee behavior. Limitations: This research was conducted on five renowned government tourism sites in the Plateau State; private tourism sites/recreation facilities could be included. Contributions: This study recommends that managers of tourist sites should incorporate intrinsic and extrinsic motivational practices to stimulate positive employee work outcomes that will, in turn, enhance the sustainability of tourist site resources and offer a welcoming, memorable, and friendly experience to tourists.